E-services computer system for UiTM student in Shah Alam / Siti Sara Zakaria @ Mustafa - Zakaria @ Mustafa, Siti Sara (Faculty of Computer and Mathematical Sciences, 2007)
E-Services Computer system (ESC) is an online service of renting computer and providing computer maintenance information. ESC has been set up to give companies that provide computer services an easy of putting their renting computer information and view computer maintenance status. TWs ESC was there to put companies that provide computer services and student can make computer services like computer renting by company selected. This project aims to create a system where any company can adding their computer rent information and student can choose company to make services. The company also can put computer maintenance status to the student and student can view the maintenance status either under maintenance or done. The E-Services Computer System is an alternative ^proach that allowed company can put their computer services and student can make their services within this system. This project is using the behavior of common computer services as an approach, which is allowed user to list, select, view the renting computer and computer maintenance information through online. A user interface for E-Service Computer System was developed using Macromedia Dreamweaver and the interfaces of the system were designed using Adobe Photoshop, SwishMAX and Macromedia Flash MX. PHP: Hypertext Preprocessor is being used as a programming language platform for designing and developing this system. MySQL is the database programs that been used in this system and it was create for developing and support complete management database. As the conclusion, E-Services Computer System will take advantage of new content and delivery technology to enable E-Services Computer system provide renting computer listing and information service.